Cost Impacts of the Inclusion of Air Transport into the European Emissions Trading Scheme in the Time Period 2012-2020 - Scheelhaase, Janina; Schaefer, Martin; Grimme, Wolfgang; Maertens, Sven (European Journal of Transport and Infrastructure Research, 2012)
Since January 2012, international aviation has been included in the emissions trading scheme of the European Union (EU ETS), in accordance with EU Directive 2009/29 EC. From this year up to (at least) 2020, all flights starting from or landing at European airports are subject to the EU ETS, apart from a few exemptions. In 2012, the CO2 emission target for aviation is 97 per cent of the historical emissions of the years 2004-2006. From 2013 onwards, this reduction target will be lowered by another 2 per cent. In September 2010, the ICAO Assembly agreed to an exemption clause for market-based measures which could be applied to the EU ETS. Whether this should be the case is a controversial issue on the international political level. Model-based empirical estimations presented in this study indicate significant impacts of the EU ETS on airline costs, airfares and competition within the airline sector: in the year 2020, more than 50 per cent of the required allowances will have to be purchased by the airlines. Assuming an allowance price of 20 € per tonne of CO2, the resulting costs for the aviation sector will amount to about 20,502 million € in 2012-2020. In addition, competitive distortions can be expected if the ICAO exemption clause is introduced to the EU ETS.